Book Publishing in the Context of Digital Economy: A Statistical Analysis - O. O. Horobets (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
In the era of the digital economy, books should continue to be relevant to modern society, and book publishing needs to be a competitive industry in the market. Therefore, the statistical analysis of world book publishing is necessary to determine the landmark movement for domestic publishers supposed to find a solid niche in the digital economy.Book publishing is an economic activity which effectiveness is measured by not only publication figures but by the level of education and consciousness of the nation, demonstrating its intellectual capacity to the whole world.The article gives an example of a successful online Amazon business. The state of popularity of the e-book in France, Korea, and China is investigated. A statistical analysis of book publishing of Ukraine is presented. The dynamics of the increase of Internet subscribers in the territory of Ukraine was observed. The dynamics of the main indicators presented in the tables is simulated. The simulation results showed that the time dependence of the number of published books and brochures, as well as the total circulation of publications, is best described by the polynomial of the fourth degree, Internet subscribers – the polynomial of the third degree. Summarizing the analysis, it was concluded that the years 2014 and 2015, when indicators and number of publications and circulation have rapidly decreased, are critical for book printing, as well as for almost all spheres of life of Ukraine, the first – from 26323 thousand units. in 2013 to 19958 thousand units. in 2015, the circulation during this time decreased by almost one and a half times. Taking into account the number of the population of Ukraine as of 2017 (44.03 million people), the indicators of the book publishing industry can be argued that the index of bookkeeping of Ukraine by 2017 was 1.02 books per person.